Experimental Investigations on the Wear Behaviour of Eutectic Al-7075/CNT/Graphite Composites Manufactured by a Combination of Two-Stage Stir and Squeeze Casting Techniques. (8th March 2022) - Swamy, Amit; Shamitha, C.; Singh, Manoj Kumar; Rinawa, Moti Lal; Kumar, K. V. Pradeep; Al Obaid, Sami; Mahadik, Mahadeo A.; Alfarraj, Saleh; Markos, Mebratu
Abstract : The dry sliding wear performance of eutectic Al-7075-CNT-Gr composites was estimated using a pin-on-disc wear test. According to the results, the wear and friction coefficients dropped gradually as the weight % of graphite elements improved. The composite's wear resistance increased significantly as the sliding speed increased from 1 m/s to 2 m/s at 49 N while the load remained constant. 7075-7.5 wt percent Gr amalgamated, on the other hand, had a more significant coefficient of friction as the sliding speed increased from 1 m/s to 2 m/s at 49 N. After the test, the researchers looked at how the worn-out surfaces of the specimens originated. The mechanically mixed layer of oxides and iron was used as an effective tribolayer to increase the wear resistance at more incredible sliding speeds in the wear test.